2005
DOI: 10.1002/ejoc.200400529
|View full text |Cite
|
Sign up to set email alerts
|

End‐Capped, Conjugated (Dimethylamino)naphthyl Nanostructures with Alternating (1‐Naphthylethynyl‐p‐phenylethynyl)x Branches on a 1,3,5‐Substituted Benzene Core

Abstract: Alternating (1‐naphthylethynyl‐p‐phenylethynyl)x 1,3,5‐trisubstituted benzene dendrons were efficiently synthesised by the heterocoupling reaction between (1‐naphthylethynyl‐p‐phenyl)xacetylene (x = 1) and 1,3,5‐triiodobenzene in the presence of a palladium‐copper catalyst system. A longer terminal acetylene chain (x = 2) was obtained from the heterocoupling between 1,3,5‐tri(1‐ethynyl‐5‐naphthylethynyl)benzene and the appropriate iodoaryl derivative. The alternating chains, and their dendron structures, show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The naphthalenethynylene-type polymers or oligomers were the outstanding representatives, for different ways can be used to link the naphthalene units [28,29]; e.g., Rodriguez and co-workers have successfully synthesized large numbers of naphthalenethynylene-type oligomers, such as 1,5-naphthalene nanostructures [30,31], 1,5-bis(p-phenylethynyl)naphthalene nanostructures [31] and a series of end-capped, conjugated (dimethylamino) naphthyl nanostructures with alternating (1-naphthylethynyl-p-phenylethynyl) x branches on a 1,3,5-or 1,4substituted benzene core [32][33][34][35], and indicated that these oligomers exhibited excellent quantum yields for the fluorescent emission. However, poor solubility of these oligomers remained the most serious problem.…”
Section: Introductionmentioning
confidence: 99%
“…The naphthalenethynylene-type polymers or oligomers were the outstanding representatives, for different ways can be used to link the naphthalene units [28,29]; e.g., Rodriguez and co-workers have successfully synthesized large numbers of naphthalenethynylene-type oligomers, such as 1,5-naphthalene nanostructures [30,31], 1,5-bis(p-phenylethynyl)naphthalene nanostructures [31] and a series of end-capped, conjugated (dimethylamino) naphthyl nanostructures with alternating (1-naphthylethynyl-p-phenylethynyl) x branches on a 1,3,5-or 1,4substituted benzene core [32][33][34][35], and indicated that these oligomers exhibited excellent quantum yields for the fluorescent emission. However, poor solubility of these oligomers remained the most serious problem.…”
Section: Introductionmentioning
confidence: 99%